Exosome‐encapsulated miR‐6089 regulates inflammatory response via targeting TLR4. Issue 2 (21st August 2018) - Xu, Donghua; Song, Meiyan; Chai, Chunxiang; Wang, Jinghua; Jin, Chengwen; Wang, Xiaodong; Cheng, Min; Yan, Shushan
Abstract : Exosome‐encapsulated microRNAs (miRNAs) have been identified as potential biomarkers in autoimmune diseases. However, little is known about the role of exosome‐delivered miRNAs in rheumatoid arthritis (RA). In this study, we investigated the profile of specific exosomal miRNAs by microarray analysis of serum exosomes from three patients with RA and three healthy controls. Quantitative real‐time PCR (qRT‐PCR) was performed to validate the aberrantly expressed exosomal miRNAs. A total of 20 exosome‐encapsulated miRNAs were identified to be differently expressed in the serum of patients with RA compared with controls. Interestingly, we found that exosome‐encapsulated miR‐6089 was significantly decreased after validation by qRT‐PCR in serum exosomes from 76 patients with RA and 20 controls. Besides, miR‐6089 could inhibit lipopolysaccharide (LPS)‐induced cell proliferation and activation of macrophage‐like THP‐1 cells. TLR4 was a direct target for miR‐6089. MiR‐6089 regulated the generation of IL‐6, IL‐29, and TNF‐α by targetedly controlling TLR4 signaling. In conclusion, exosome‐encapsulated miR‐6089 regulates LPS/TLR4‐mediated inflammatory response, which may serve as a novel, promising biomarker in RA. Abstract : TLR4 is a direct target for miR‐6089. MiR‐6089 regulates the generation of IL‐6, IL‐29, and TNF‐α by targetedly controlling the TLR4 signaling.